All quiet on the Eastern front? Disruption scenarios of Russian natural gas supply to Europe - Philipp M. Richter; Franziska Holz (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The Russian-Ukrainian crisis has revitalized the European concerns of supply disruptions of natural gas as experienced in 2006 and 2009. However, the European supply situation, regulation and infrastructure have changed since: imports aremore diversified, EU member states better connected and a common regulation on the security of supply has been introduced. Nevertheless, several East European countries are highly dependent on Russian natural gas. This paper investigates different Russian natural gas export disruptions scenarios and analyses short- and long-term reactions to ensure a sufficient supply of natural gas within Europe. We use the Global Gas Model (GGM), a large-scale mixed complementarity representation of the natural gas sector with a high-level of technical granularity with respect to storage and transportation infrastructure. We find that most of the EU member states are not severely affected by a complete drop out of Russian exports. Removing infrastructure bottlenecks within the EU should still be prioritized in order to secure a sufficient natural gas supply for all EU member states.
Keywords: Q34; Q37; Q41; C61; L95; 330; natural gas trade; Russia; Europe; security of supply; infrastructure investment; equilibrium modelling